Prevalence of influenza vaccination among health care workers and adverse effects after vaccination: A cross-sectional study - Uğraş Dikmen, Asiye; Baran Aksakal, Fatma Nur; Aycan, Zehra; Aycan, Sefer (Journal of Surgery and Medicine, 2019)
Aim: Influenza is an important public health problem for the whole world and the prevalence of influenza vaccination is low.The aim was to determine the prevalence of influenza vaccination and adverse effect after seasonal influenza and/or pandemic A (H1N1) influenza vaccination in health care workers (HCW) working in Ankara. Methods: It is a cross-sectional study. In March-April 2010, 1611 HCW from Atatürk Hospital, Sami Ulus Hospital and 13 Primary Health Care centers have been reached and survey was conducted. Results: 41.1% of HCW have had seasonal influenza vaccination and 26.1% of them had side effects. Most of HCW, who have not been vaccinated; reported the needlessness of vaccination and fear of side effect as explanation of reason for being not vaccinated. 46.6% of examined HCW had pandemic influenza vaccination. After pandemic influenza vaccination, any of side effect was seen in 66.4% of vaccinated HCW. Most of HCW, reported the needlessness of vaccination, fear of side effect, inability to vaccinate, debates and contradictions on the views, as explanation of reason for being not vaccinated. Conclusion: As a result, vaccination percents are under expected. HCW, like every part of public, are affected from actual discussions. For health services being not affected from these conditions, HCW’s knowledge should be renewed and updated.